Sinkronisasi Perencanaan, Penganggaran dan Pengawasan: Peta Jalan Menuju Keberhasilan Pembangunan (Studi Pada Pemerintah Provinsi Nusa Tenggara Timur) - Nur Effendi, Wahyuni; Devina Agustin Hake, Stephanie; Rozikin, Mochammad (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study examines the synchronization of the three pillars of performance planning, budgeting, and oversight in the regional development process of East Nusa Tenggara Province (NTT). Failure to integrate these three elements can lead to inconsistencies in development documents, potentially hindering the achievement of development targets. This research uses a descriptive quantitative approach to analyze the oversight results on the consistency between planning and budgeting documents for 2025 in East Nusa Tenggara Province. The findings indicate that despite efforts to improve consistency, significant discrepancies exist, especially in aligning performance indicators and budget ceilings, due to limited oversight of the budget, suboptimal interagency coordination, and the influence of political pressure. The proposed recommendations include implementing data-based planning, strengthening human resource capacity, increasing public participation, and integrating electronic systems to support transparency and accountability in the development process. It is hoped that the results of this study can guide the regional government of NTT Province in achieving more efficient and sustainable development.